ANALISIS PENGARUH KUALITAS WEBSITE PT TIKI JALUR NUGRAHA EKAKURIR (JNE) TERHADAP KEPUASAN PENGGUNA DENGAN METODE WEBQEM - Sulistiowati Sulistiowati; Tony Soebijono; Fajriyan Nurli (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2018)
P.T. JNE has implemented an official website with a www.jne.co.id address in which there are various menus that can be utilized by visitors, ie company profile, products and services, agency business solutions, career vacancies, to tracking shipment and shipping rates The influence of website quality on website P.T. JNE to user satisfaction will be analyzed in this study based on end user perception using webqem method. The data to be used in this research is by using an offline questionnaire. Then will be analyzed using variable from webqem method using some test that is like test of validity, reliability, assumption test and linear regression test. This research yields conclusion that usability, functionality, reliability, and efficiency have positive and significant influence to user satisfaction with influence of 63,2%, the rest (100% 63.2%) = 36.8% is the other variable not included in this research.